High Parasitic Contamination of Soil Samples in the North of Iran: A Potential Risk of Parasitic Infection for Tourists - Haghparast-kenari, Beheshteh; Nayeri, Tooran; Sarvi, Shahabeddin; Rahimi, Mohammad T.; Ahmadpour, Ehsan; Sharif, Mehdi; Daryani, Ahmad (Infectious Disorders - Drug Targets, 2021)
Background: Soil-transmitted parasites (STPs) are significant intestinal parasites that infect humans and animals and impose considerable burdens on human society and animal husbandry industries. Therefore, the present study aimed to determine the prevalence of parasitic elements of soil samples collected from the north of Iran. Methods: A total of 256 soil samples were collected from public parks, public places, vegetable gardens, sand heaps, and shadow areas near houses in the north of Iran and examined using the sucrose flotation method. Results: Out of 256 examined samples, 131 (51.2%) showed parasitic contamination, including larvae (43%), oocysts (14.1%), and different eggs (6.6%). According to the results, the most and least common parasites observed in the samples were larvae (43%), as well as Toxascaris leonina, and Trichuris trichiura (0.4%), respectively. Moreover, the most and least contaminated locations were sand heaps (62.5%) and shadow areas near houses (45.6%), respectively. Regarding cities, Behshahr (68.3%) and Sari (67.5%) had the highest contaminated soil samples, whereas Chalus (37.5%) showed the lowest contamination. On the other hand, rural samples showed more contamination compared to urban areas (P< 0.05). Conclusion: The findings of the present study indicate that the overall prevalence of STPs in examined areas and highly contaminated soil samples can be considered as a potential source of human contamination particularly tourists with STPs.
Keywords: public place